Simulation and Visualization of Hair for Real-Time Games - Hällman, Mathias (My University, 2011)
This report presents an implementation of techniques for hair simulation and rendering meant to be run in real-time along side everything else in a performance heavy game by modern standards. The simulation method is derived from a mass-spring system with added functionality to maintain a default pose and collide against the head while staying stable even at noninteractive frame rates. Patches of hair are extracted from a polygonal model of the hair. These patches are then sorted against the head in order to render them in the proper order for alpha blending to be performed correctly. A specialized hair shading model is also presented. The results of the implementation show only a small drop in performance, which arguably is out-weighted by the pleasing visual results of having livelier hair for the ingame characters. Sammanfattning Denna rapport presenterar en implementation av tekniker för hår-simulering och rendering ämnade för att köras tillsammans med resten av ett prestanda-krävande spel med dagens standard. Simulerings-metoden är härledd från mass-spring-system med till-lagd funktionalitet för att behålla en standard pose samt kollidera mot huvudet medan systemet hålls stabilt även med icke-interaktive frame rates. Patchar av hår är extraherade från en polygonmodell av håret. Dessa patchar sorteras sedan mot huvudet för att uppnå lämpling renderings-ordning för alpha blending att utföras korrekt. En specialiserad hår-shadingmodell presenteras också. Resultaten från implementationen visar endast en liten minskning i prestandan, vilket diskuterbart vägs ut av de tillfredsställande visuella resultaten av att ha livligare hår för in-game-karaktärerna.
Keywords: Datorteknik; Computer Engineering